Obstrução pilórica por corpo estranho em cão pinscher: relato de caso - Brito, Bruna Wanderley Raymond de (Universidade Federal Rural do Semi-Árido, 2018)
The compulsory supervised stage, an important step towards the conclusion of the Veterinary Medicine course at the Federal Rural Semiarid University (UFERSA), was conducted interdisciplinarily in the area of Small Animal Clinical Medicine and in the Diagnostic Imaging of Companion Animals area under the orientation of Prof. Dr. Wirton Peixoto Costa. The objective was to follow the clinical cases sent to the Animal Imaging Diagnostics sector and to report the activities developed, deepening the knowledge about foreign body obstruction in dogs through Diagnostic Imaging. The Obligatory Supervised Internship (ESO) was carried out at the Federal Rural Semiarid University (UFERSA), at the Veterinary Hospital Jerônimo Dix-Huit Rosado Maia (HOVET), during the period from December 4, 2017 to March 6, 2018, totaling cargo hour of 240 hours. The internship allowed the application of theoretical knowledge, acquiring great practical experience and contributing to the professional training through the experience and the follow-up of the various clinical cases attended in HOVET. A case of a canine male, Pinscher breed, 1 year and 4 months old, weighing 2.7 kg was described, presenting with emesis, bloody diarrhea and severe abdominal pain, where the ingestion of household waste by the animal had been reported. The ultrasound examination, together with simple and contrast-enhanced radiographs confirmed the diagnosis of foreign body obstruction (mechanical ileus).
Monografia
Keywords: Obstrução intraluminal; Ingestão de corpo estranho; Canino; Íleo Mecânico; Intraluminal Obstructiono; Freign Body Intake; Canine; Mechanical Ileum; CIENCIAS AGRARIAS::MEDICINA VETERINARIA